Differential Morphological, Structural and Biological Characteristics of Cysts in Heterodera Species in Korea - Han, Ga Ram; Kang, Heonil; Choi, In Soo; Kim, Donggeun; Yun, Hye Young; Kim, Young Ho (The plant pathology journal, 2020)
Morphological (cyst shape, color, and sizes [length (L), maximum width (W), volume and "a" (L/W)]), structural (vulvar cone slope angle [VCSA], surface wrinkle [VCSW], cyst wall thickness, composition, and texture) and biological characteristics (fecundity, hatching, and emergence [number of second-stage juveniles (J2) from a cyst]) in preceding (Hg), currently-recorded (Hs) and (Ht) were examined by microscopy. Cysts were lemon-shaped, indicating the genus is except for Hs that formed frequently globular cysts with significantly flatter VCSA (102.2°) with smooth VCSW than Hg (50.6°) and Ht (82.0°), but not genus because of the presence of vulvar cone in Hs. Ht was significantly larger in all morphological characteristics than Hg and Hs, suggesting Ht may be diagnosed differentially by cyst sizes and also host plant preferences. Hs showed smaller "a" value with more globular shape and stronger structures with more thickened and strengthened collagen-like texture of cyst wall than Hg and Ht. This suggests Hs may be diagnosed differently by structural characteristics from the others, especially Hg with similar cyst sizes. There were no significant differences in emergence (inoculum potential) among cyst nematodes due to the offset of fecundity and hatching rate; however, the inoculum potential of Hs may be not so persistent as Hg and Ht in fields because of its lower fecundity and higher hatching rate (causing rapid inoculum loss) than the others. These characteristics of cysts provide information useful for simple and differential diagnoses and reliable management of cyst nematodes.